Asset Tangibility, Efficiency And Firm Value: Evidence From Nigeria (Eurasian Journal of Humanities and Social Sciences, 2025)
The study examined the relationship between Asset tangibility, efficiency and firm value of manufacturing firms listed on Nigeria Stock Exchange between 2018 and 2023. Census sampling technique covering food and beverages, cement and pharmaceutical subsector was used to determine sample size of 22 firms from a population of Sixty-five manufacturing firms with complete data listed on the Exchange. Descriptive statistics and Multiple Regression technique was used for analysis of data while Hausamann test for selection of model was adopted. Various Classic assumption and diagnostic tests were carried out on data set reliability of result. The study found positive significant relationship of firm efficiency with Tobin q with a positive co-efficient 80986.87 and statistically significant p=0.000 0.05 indicating a positive insignificant relationship of asset tangibility with price earnings ratio. Result also showed efficiency has positive co-efficient 1.20851 and p-value of 0.0009< 0.05 indicating a negative significant relationship of asset tangibility with Enterprise Value. From the result, we found reverse directional relationship between Efficiency and Asset tangibility on firm value measured by Enterprise value and Tobin Q. We conclude increased Asset tangibility dampens efficiency and vice versa thereby indicating a trade-off of the two firm characteristics. Inflation positively and significantly relates with TOBIN Q and Price earning ration implying increase in inflation increase market value and the ability of firm to convert earnings to market price. Inflation negatively affects Enterprise value. We conclude that Inflation as a Macroeconomic factor affects firm value. We recommend managers should improve efficiency and manage trade-off between asset tangibility and efficiency to maximise shareholders wealth